2016
DOI: 10.1021/acs.jpcb.6b07142
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside-Lipid and Ganglioside-Protein Interactions Revealed by Coarse-Grained and Atomistic Molecular Dynamics Simulations

Abstract: Gangliosides are glycolipids in which an oligosaccharide headgroup containing one or more sialic acids is connected to a ceramide. Gangliosides reside in the outer leaflet of the plasma membrane and play a crucial role in various physiological processes such as cell signal transduction and neuronal differentiation by modulating structures and functions of membrane proteins. Because the detailed behavior of gangliosides and protein-ganglioside interactions are poorly known, we investigated the interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 96 publications
7
105
0
1
Order By: Relevance
“…To this end, web‐based user‐friendly Martini‐Maker is developed to construct flat bilayers, vesicles, micelles, and nanodiscs with minimal user inputs. We have shown that the resulting structures are robust and similar compared to their atomistic counterparts, although there is room for improvement (i) by optimizing the Martini parameters for Ca 2+ and by reducing the overall stickiness of sugar‐based molecules as was recently performed for gangliosides and (ii) the Martini‐Maker system building parameters to better estimate the number of lipid molecules in Vesicle Builder . Martini‐Maker is expected to replace the laborious process of manual system setup of these complex LPS‐containing systems with an easy to use, freely available, online procedure that requires minimal manual intervention.…”
Section: Discussionmentioning
confidence: 96%
“…To this end, web‐based user‐friendly Martini‐Maker is developed to construct flat bilayers, vesicles, micelles, and nanodiscs with minimal user inputs. We have shown that the resulting structures are robust and similar compared to their atomistic counterparts, although there is room for improvement (i) by optimizing the Martini parameters for Ca 2+ and by reducing the overall stickiness of sugar‐based molecules as was recently performed for gangliosides and (ii) the Martini‐Maker system building parameters to better estimate the number of lipid molecules in Vesicle Builder . Martini‐Maker is expected to replace the laborious process of manual system setup of these complex LPS‐containing systems with an easy to use, freely available, online procedure that requires minimal manual intervention.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the wide range of domain features that lipid-lipid interactions can generate in molecular simulations of simple and complex bilayers, it is not so surprising to unveil such a diversity of lipid domains in living cell membranes. As a matter of fact, lipid clusters in simulated membranes show various (i) composition, as they are not only enriched in SM and chol, but also in gangliosides (GM1 and GM3) and in PC analogs [44,45]; (ii) lipid order; and (iii) topography, as some GM3 nano-clusters have been shown to preferentially associate with concave (when viewed from the extracellular medium) membranes [46]. Such lipid domain diversity is also supported by several experimental data on simple lipid mixtures [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…head group, acyl chain length and saturation [50]). Moreover, lipid domain biogenesis and/or maintenance also depend on the chol content, as chol is a key regulator of membrane fluidity (and thus space between phospholipids for optimal head group interactions) and is able to directly interact with SM or GM1 [45,51].…”
Section: Discussionmentioning
confidence: 99%
“…A comparable analysis of our equilibrium CG simulations yielded a free energy of interaction of -6 kJ/mol. Given the detailed differences between the various studies, a conservative interpretation would be that cholesterol interactions with GPCRs are of the order of -5 to -10 kJ/mol, in contrast with estimated free energies of -10 to -40 kJ/mol for the interactions of a range of different membrane proteins with anionic phospholipids calculated by the same approach (see (Arnarez et al, 2016;Domański et al, 2017;Domicevica et al, 2018;Gu et al, 2017;Hedger et al, 2016a;Hedger et al, 2016b) and Table S1).…”
Section: Discussionmentioning
confidence: 99%